Pengaruh Tingkat Pendidikan, Kesadaran dan Lingkungan Terhadap Kepatuhan Wajib Pajak Orang Pribadi. (Studi Kasus pada KPP Pratama Kota Kediri Tahun 2021) - Putri Elsa Meilina; M. Cholid Mawardi; Siti Aminah Anwar (e_Jurnal Ilmiah Riset Akuntansi, 2023)
Tax is a mandatory contribution to the state that is coercive and used for national development for the welfare of the people. This study aims to analyze the Level of Influence of Education, Awareness and the Environment on Individual Taxpayer Compliance with Case Studies at KPP Pratama Kota Kediri in 2021. This type of research is quantitative research. Sampling used a simple random sampling technique and was measured using the slovin formula. The sample in this research is 100 participants. Multiple linear regression using the SPSS version is the technique. 29.00. The outcomes demonstrated that the variable level of education had no partial effect, Awareness had a positive and significant effect, and the environment had no partial effect.Keywords: Education Level, Awareness, Environment and Taxpayer Compliance